Self-regulated learning based-STEM model: How it impacts students’ self-directed learning in physical education classes - Eva Sri Gumilang; Tri Martini; Dian Budiana (Journal Sport Area, 2022)
The low level of self-directed learning among students is a problem in this study and the limited research on Science, Technology, Engineering, and Mathematics-based Self-Regulated Learning in physical education is a gap in this research. Science, Technology, Engineering, and Mathematics (STEM) based on Self-Regulated Learning (SRL) is an alternative learning model in Physical Education. The purpose of this study was to determine the effect of application Science, Technology, Engineering, and Mathematics based Self-Regulated Learning to develop self-directed learning. This study used quasi-experimental method with a nonequivalent control group design and sampling used purposive sampling technique. The participants in this study were students VIII grade. Research was conducted in SMP Laboratorium School UPI with online learning and Limited Face-to-Face Meeting. The instruments of this study used the Self-Rating Scale of Self Directed Learning (SRSSDL). After the sample had completed the treatment, the results of data analysis showed that directed learning aspect was 0.027 with the criterion value (Sig.) = 0.05. Regardless of the results, this is supported by empirical evidence from student behavior, learning, and task making. They showed the development of students' abilities in the learning process did not depend on teachers, friends, class conditions and others. It can be concluded that implementation of Science, Technology, Engineering, and Mathematics (STEM) based on Self-Regulated Learning (SRL) has an effect on develop self-directed learning. This research contributes to learning innovation in physical education, so that teachers can apply this model on an ongoing basis to develop self-directed students. Future research needs to be done, for example trying to apply this model to develop other potentials in students such as motivation, cooperation, or responsibility.